Proceedings of the 30th Annual ACM Symposium on Applied Computing 2015
DOI: 10.1145/2695664.2695825
|View full text |Cite
|
Sign up to set email alerts
|

Profiling energy profilers

Abstract: While energy is directly consumed by hardware, it is the software that provides the instructions to do so. Energy profilers provide a means to measure the energy consumption of software, enabling the user to take measures in making software more sustainable. Although each energy profiler has access to roughly the same data, the reported measurements can differ significantly between energy profilers. In this research, energy profilers are evaluated through a series of experiments on their functionality and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Software‐based approaches can be roughly categorized in 2 sets: source code instrumentation and energy profilers . Source code instrumentation consists in injecting profiling code into the applications code (or byte code), to capture all the necessary events related to EC.…”
Section: Related Workmentioning
confidence: 99%
“…Software‐based approaches can be roughly categorized in 2 sets: source code instrumentation and energy profilers . Source code instrumentation consists in injecting profiling code into the applications code (or byte code), to capture all the necessary events related to EC.…”
Section: Related Workmentioning
confidence: 99%
“…A more simple software-only approach is to use energy profilers [26]; software tools including a power model with the ability to estimate the software EC on different levels of granularity. Unfortunately recent study has found energy profilers to not always provide the desired results [14].…”
Section: Energy Consumption Measurementsmentioning
confidence: 99%
“…Pro (WUP) capable of measuring the total power drawn by an entire system with a one second interval, measured the power drawn by the test server and performance data was collected using Perfmon, a standard performance monitoring tool with Microsoft Windows. A different deployment could require a more software intensive approach using, e.g., energy profilers [14]. Finally, the client system was used to trigger the required activity and data was collected remotely (i.e.…”
Section: Case Study: Applying the Perspective In Practicementioning
confidence: 99%
See 2 more Smart Citations